Inventarisasi Semut Subfamili Formicinae di Kawasan Cagar Alam Lembah Anai, Kabupaten Tanah Datar, Sumatera Barat - Pradani Eka Putri; Henny Herwina; Dahelmi Dahelmi (Jurnal Biologi Universitas Andalas, 2015)
An inventory of ants from subfamily Formicinae at Lembah Anai Nature Reserve, West Sumatra was conducted from June to November 2013. Quadra Protocol methods were used to collect ant samples, i.e; hand collecting, honey bait trap, soil core sampling and leaf litter sifting along two 180 m transects. Those methods were applied at two different habitats (forest edge and forest interior). We found 163 individuals of Formicinae which belong to 23 species, 8 genera and 3 tribes. Each species was described based on morphological characteristics. Keywords: ants, Formicinae, identification, Lembah Anai Nature Reserve